2018
DOI: 10.1115/1.4041966
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Biomechanical Properties and Microstructure of Trabeculae Carneae, Papillary Muscles, and Myocardium in the Human Heart

Abstract: Trabeculae carneae account for a significant portion of human ventricular mass, despite being considered embryologic remnants. Recent studies have found trabeculae hypertrophy and fibrosis in hypertrophied left ventricles with various pathological conditions. The objective of this study was to investigate the passive mechanical properties and microstructural characteristics of trabeculae carneae and papillary muscles compared to the myocardium in human hearts. Uniaxial tensile tests were performed on samples o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 75 publications
1
19
0
Order By: Relevance
“…This procedure has been described in the mechanical tests of cardiac tissues [17,[22][23][24][25][26][27][28][29]. The number of preconditioning cycles in the biaxial/uniaxial tests varied among 5-10 cycles for the animal (canine, bovine, and murine) myocardium [17,22,[24][25][26][27][28][29], whereas Sommer et al and Fatemifar et al showed that, after 3-5 cycles, the human heart tissue reached stable biaxial behavior [23,30]. Owing to the viscoelastic nature of the tissue, a sufficient resting period should be given between the tests.…”
Section: Preconditioning and Residual Stress Measurementmentioning
confidence: 99%
See 2 more Smart Citations
“…This procedure has been described in the mechanical tests of cardiac tissues [17,[22][23][24][25][26][27][28][29]. The number of preconditioning cycles in the biaxial/uniaxial tests varied among 5-10 cycles for the animal (canine, bovine, and murine) myocardium [17,22,[24][25][26][27][28][29], whereas Sommer et al and Fatemifar et al showed that, after 3-5 cycles, the human heart tissue reached stable biaxial behavior [23,30]. Owing to the viscoelastic nature of the tissue, a sufficient resting period should be given between the tests.…”
Section: Preconditioning and Residual Stress Measurementmentioning
confidence: 99%
“…While the uniaxial mechanical test offers a quicker and easier examination of the material mechanical property, the biaxial mechanical test better mimics the in vivo loading conditions and provides more comprehensive measurements of the anisotropic mechanical behavior [17,19,20,22,[39][40][41]. Both methods have been used in prior studies of LV and RV mechanical properties [17,20,[22][23][24][25][26][27][28][29][30][39][40][41][42][43][44][45][46] (please see Table 1 for a summary of these studies).…”
Section: Uniaxial and Biaxial Tensile Mechanical Testsmentioning
confidence: 99%
See 1 more Smart Citation
“…The dimensions and composition of the strain sensors were chosen such as to match the Young modulus ( E ) of the myocardium up to 600 kPa. [ 28 ] Figure S9c,d, Supporting Information show the mechanical properties of Sensor 1 and Sensor 2, each one with E = 666 kPa and E = 647 kPa, respectively. In addition, a similar procedure is currently used for the attachment of temporary defibrillators without showing any severe adverse effects.…”
Section: Resultsmentioning
confidence: 99%
“…Trabeculae and papillary muscles are typically employed as proxies for the myocardium in the investigation of cardiac ventricular mechanics as they are linearly arranged, present throughout both ventricles of the heart, and are thought to be roughly homologous with the ventricular free walls and septum ( Goo et al, 2009 ), however, small ventricular wall strips have also been used ( Fatemifar et al, 2018 ). It is important to describe the origin of the muscle tissue (papillary, trabecular or free wall) as it has recently been shown that trabeculae are stiffer than either papillary muscles or myocardial strips from the same heart ( Fatemifar et al, 2018 ), and can contain more collagen. Additionally, RV tissues have been shown to be stiffer than LV tissues ( Sacks and Chuong, 1993 ; Fatemifar et al, 2018 ).…”
Section: Methodsmentioning
confidence: 99%